Controlled Expansion of a Strong‐Field Iron Nitride Cluster: Multi‐Site Ligand Substitution as a Strategy for Activating Interstitial Nitride Nucleophilicity. Issue 40 (24th May 2018) - Drance, Myles J.; Mokhtarzadeh, Charles C.; Melaimi, Mohand; Agnew, Douglas W.; Moore, Curtis E.; Rheingold, Arnold L.; Figueroa, Joshua S.
Abstract: Multimetallic clusters have long been investigated as molecular surrogates for reactive sites on metal surfaces. In the case of the μ4 ‐nitrido cluster [Fe4 (μ4 ‐N)(CO)12 ] −, this analogy is limited owing to the electron‐withdrawing effect of carbonyl ligands on the iron nitride core. Described here is the synthesis and reactivity of [Fe4 (μ4 ‐N)(CO)8 (CNAr Mes2 )4 ] −, an electron‐rich analogue of [Fe4 (μ4 ‐N)(CO)12 ] −, where the interstitial nitride displays significant nucleophilicity. This characteristic enables rational expansion with main‐group and transition‐metal centers to yield unsaturated sites. The resulting clusters display surface‐like reactivity through coordination‐sphere‐dependent atom rearrangement and metal–metal cooperativity. Abstract : Growth plan : Replacement of multiple CO ligands in the strong‐field cluster [Fe4 (μ4 ‐N)(CO)12 ] − with more strongly donating ligands turns an otherwise unreactive interstitial nitride into a good nucleophile. This emergent property enables the systematic incorporation of reactive sites into the cluster framework in a manner reminiscent of the introduction of defect sites on heterogeneous surfaces.